Collaborative Conflict Management: An Open Communication Approach to Resolving Conflicts Among Students at SMK Negeri 2 Buton and SMA Negeri 2 Pasarwajo - Muliadin Oba; La Didi; Asmiddin Asmiddin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines collaborative conflict management among students at SMK Negeri 2 Buton and SMA Negeri 2 Pasarwajo, emphasizing the role of open and coordinated communication in resolving inter-student conflicts. Conflicts in schools are common, particularly among adolescents who are navigating emotional development, identity formation, and social recognition. Such conflicts can manifest as relational tensions, communication misunderstandings, group identity differences, and even aggressive behavior that disrupts the school environment. The research employs a descriptive qualitative approach, utilizing in-depth interviews, participant observation, and document analysis to explore the dynamics of conflict and the strategies employed to manage it collaboratively. The findings reveal that the success of conflict resolution is strongly determined by the quality of communication. Open, coordinated, empathetic, honest, and goal-oriented communication fosters mutual understanding, reduces tension, and encourages cooperation between students and the school. Collaborative communication emerges as the key mechanism for achieving peaceful conflict resolution and harmonious social relationships within the school setting. The study also highlights that a collaborative approach is more effective in restoring social relationships than coercive or purely punitive strategies, as it emphasizes dialogue, empathy, and mutual understanding. Furthermore, coordination among school actors ensures that messages remain consistent, prevents further misunderstandings, and strengthens institutional support for sustainable conflict management. The study contributes to the literature on educational conflict resolution by demonstrating that collaborative communication is essential not only for resolving immediate conflicts but also for promoting long-term relational stability and a positive school climate. Practical implications suggest that schools should foster a culture of open, empathetic, and structured communication while coordinating across stakeholders to prevent recurrence of inter-student conflicts.